2019
DOI: 10.1007/s11899-019-00548-2
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitor Therapy Discontinuation for Patients with Chronic Myeloid Leukaemia in Clinical Practice

Abstract: Purpose In chronic myeloid leukaemia, tyrosine kinase inhibitor treatment is traditionally given continuously for life. However, these drugs produce excellent responses for many patients, and this is accompanied by survival that is close to normal. This has prompted studies of whether it is possible to stop treatment, thus achieving a treatment-free remission (TFR). Recent Findings Most TFR studies have focussed on abrupt cessation in patients with long-standing deep remissions, but recent data suggest that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
2
32
0
1
Order By: Relevance
“…In the case of patients who discontinued TKI treatment side effects might have been related to the occurrence of a withdrawal syndrome [1,2]. Although being considered mostly low grade, these effects cause considerable discomfort and affect a patients' QoL [1,2,8,18]. Similar to other studies [20][21][22][23][24][25], in the present survey patients rated the absence of side effects the most important benefit of TKI treatment discontinuation.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In the case of patients who discontinued TKI treatment side effects might have been related to the occurrence of a withdrawal syndrome [1,2]. Although being considered mostly low grade, these effects cause considerable discomfort and affect a patients' QoL [1,2,8,18]. Similar to other studies [20][21][22][23][24][25], in the present survey patients rated the absence of side effects the most important benefit of TKI treatment discontinuation.…”
Section: Discussionsupporting
confidence: 73%
“…Patients eligible for TKI treatment discontinuation suffer from side effects resulting from their TKI use. In the case of patients who discontinued TKI treatment side effects might have been related to the occurrence of a withdrawal syndrome [1,2]. Although being considered mostly low grade, these effects cause considerable discomfort and affect a patients' QoL [1,2,8,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results of a long-term follow-up of the STIM study showed no patient sex-related differences in the achievement of TRF [4]. In addition, there have been no reports showing sex-related differences in the achievement of TRF in past studies where TKI was discontinued [5]. Although our study also showed no significant difference between male (3/9 [33.3%]) and female, (7/17 [41.2%]), the TFR rate was rather higher in female [1].…”
mentioning
confidence: 93%